Financial Sector Development, Government Size, Trade Openness and Economic Growth: An Emperical Analysis in ASEAN-4 Countries - Mohd Azlan Shah Zaidi; Zulkefly Abdul Karim; Zurina Kefeli (Universitas Islam Indonesia, 2005)
The main objective of this paper is to evaluate the relative impact of financial sector development, government size and trade openness of a country on its economic growth. This is done to investigate which factors play more prominent role in leading the growth of the economy. Four ASEAN countries known for their similar economic orientation, namely Ma-laysia, Thailand, Indonesia and Singapore have been selected for this purpose. To achieve the objective, a series of econometric tests is applied. These include unit root test and cointe-gration test. A vector error correction model (VECM) is then applied to capture both the short-run dynamic and the long-run equilibrium relationship between variables. Impulse response function is utilized to look at the impact of each variable on economic growth while variance decomposition is used to measure the magnitude of the impact. The results show that trade openness plays the leading role in promoting economic growth in Malaysia, Sin-gapore and Indonesia. For Malaysia financial sector development follows second and the government size comes third while for Singapore the order is reverse. For Indonesia, the government size overtakes the leading role at the later stage while the financial sector devel-opment is immaterial. For Thailand, no firm conclusion can be made, as the results are not promising. The results signify that the right policies have been taken by the selected coun-tries to promote higher economic growth. Keywords: Economic growth, financial sector development, government size, trade openness.